(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2021)
This study has aimed to measure the relationship between the skills required for the labor market and the employment of graduates of community colleges at King Khalid University. For gathering the required data, a questionnaire has been designed and distributed to the faculty members of community colleges at King Khalid University in a random sample method. The chosen sample size has covered (123) individuals. Questionnaire forms have been distributed and retrieved from (117) participants. Therefore, the estimated response has reached 95 % of the total sample size. The results of the study have shown that there is not any significant relationship between the skills which the graduates acquire and the requirements of employment. That is, the skills that the community colleges graduates acquire at King Khalid University do not affect the employment requirements. Therefore, the study has recommended the following: To strengthen the partnership between community colleges and owners of the labor market in order to know the job requirements and the skills required for them especially for the coming period. And train the graduates of those community colleges before they graduate. That is, the researchers recommend to concentrate on the practical side of training students before they graduate. And review of the contents of the current programs so as to develop the skills required for the labor market, and other tools.